2018
DOI: 10.1007/s00192-018-3710-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the anatomical position of the urethra meatus in women with recurrent post-coital cystitis: a case-control study

Abstract: Our results indicate an association between shorter urethra-vagina distance and post-coital rUTIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
2
9
1
1
Order By: Relevance
“…The results of this study showed that sexual and genital hygiene habits were associated with UTI in pregnant women after adjusting for the confounders. In this study, most of the identified risk factors for UTI were similar to those found in previous studies on the urogenital infections of non-pregnant women in the menstruating age (3,13). In accordance with these results, two observational studies evaluated the association between UTI and sexual and genital hygiene habits during pregnancy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study showed that sexual and genital hygiene habits were associated with UTI in pregnant women after adjusting for the confounders. In this study, most of the identified risk factors for UTI were similar to those found in previous studies on the urogenital infections of non-pregnant women in the menstruating age (3,13). In accordance with these results, two observational studies evaluated the association between UTI and sexual and genital hygiene habits during pregnancy.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, sexual intercourse for more than 3 times per week was related to UTI, attributing to the fact that the mechanical manner of sexual intercourse may increase the transfer of uropathogens into the urethra and bladder. This relationship was also reported for recurrent cystitis (3,9,16). However, washing the genital area and voiding after intercourse may have a preventive effect against the UTI.…”
Section: Discussionsupporting
confidence: 57%
“…To the best of our knowledge, this is the first nationwide study to elucidate the effect of BMI and height on cystitis. Previous studies, of different designs, have included some hundred to a couple of thousand cases and the results have been inconclusive 3 , 6 – 8 . Larger studies on other infections have, however, found similar results to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Cystitis is a very common urinary tract infection (UTI) in otherwise healthy fertile women 1 . The distance uropathogens must travel from the fecal reservoir to the urethra has previously been found to be related to cystitis 2 , 3 and associations with height and body mass index (BMI) have been found 2 . Although underweight and obesity have been associated with various infections 4 , 5 , only a few smaller studies have investigated BMI in relation to UTI with inconsistent results 3 , 5 8 and the effect of height on cystitis does not seem to be well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation